Dietary fats promote inflammation in Wistar rats as well as induce proliferation, invasion of SKOV3 ovarian cancer cells. Issue 5 (10th March 2020) - Saeidi, Jafar; Motaghipur, Reza; Sepehrian, Atefe; Mohtashami, Mahnaz; Forooghi Nia, Fatemeh; Ghasemi, Ahmad
Abstract: The role of high fat diet (HFD) in ovarian cancer and its underlying mechanisms are poorly known. In current investigation, we investigated inflammatory and oncogenic effect of dietary fats in female Wistar rats and ovarian cancer cell line (SKOV3). The ELISA kits were used for adipokines and inflammatory factors analyses in sera collected from rats fed with high fat diet (SR‐HFD). Cell growth, proliferation, apoptosis, migration, and invasion were measured in SKOV3 cells treated with the SR‐HFD and FA mix. IL6, IL1β, TNFα, NF‐kβ, and p53 expression were measured in cells incubated with the mentioned treatments. Leptin and inflammatory factors increased, while adiponectin decreased in SR‐HFD. Moreover, FA mix significantly induced proliferation, migration, and invasion, promoted the expression of inflammatory factors and NF‐κB and inhibited apoptosis markers in SKOV3 cells. Taken together, our findings revealed that diet might be a crucial factor in ovarian cancer progression through altering the inflammatory factors. Practical applications: The HFD‐mediated obesity promotes cancer progression in various tissues. This study highlights the progression of inflammation in female Wistar rats and the growth of ovarian cancer cells by dietary fats. Thus, dietary factors can be considered as key factors for the prevention of ovarian cancer. Abstract : HFD increases the body weight, biochemical factors, serum adipokine and inflammatory levels in Wistar rats. FA mix promotes cell growth, proliferation, migration and invasion in the SKOV3 ovarian cancer cell line. FA mix enhances the expression of inflammatory factors in SKOV3 ovarian cancer cell line.